Penanaman Perilaku Asertif Pada Anak Usia Dini Sebagai Tindak Preventif Child Grooming - Mulyana, Rijal Assidiq; Puspitasari, Ratna; Fatimah, Syifa Siti (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
The development of the digital technology has changed many things, including crime, which is based on social media. Criminals easily use digital access to commit violence against children, including child grooming. The study was conducted to find preventive measures to prevent the occurrence of child grooming crimes by collecting reference materials for analysis using a library research approach. Based on the results of the analysis, parents can take preventive actions at home and teachers at school by instilling assertive behavior in children, so that children can openly convey what they want, feel, experience, or think. Also parents and teachers will find it easier to provide education about body parts that should not be touched on children.